Facilitating intercultural negotiated practices in joint ventures: The case of a French–German railway organization. Issue 1 (February 2019) - Barmeyer, Christoph; Davoine, Eric
Highlights: Identification of synergistic cultural practices in a French–German joint venture. Analysis and categorization of negotiation processes to develop innovative cultural practices. Identification of factors which facilitate the co-construction of synergistic cultural practices. Emphasis of the role of binational boundary spanning dyads in the co-construction processes. Abstract: In this paper, we show how new work and managerial practices emerge in international joint ventures (IJVs), how they are co-constructed by cultural negotiating processes over time, and how this co-construction can provide synergistic effects. We use the case study of a binational railway organization which coordinates activities of its parent companies, DB and SNCF, between France and Germany, to focus on emerging practices, and use the framework of Brannen and Salk (2000) to categorize these practices. Our study centres on factors that facilitate the development of synergistic practices: organizational and communication structures, individual skills and socialization of IJV actors, and interpersonal relationships and learning processes in "boundary spanning dyads". Where previous studies typically insist on boundary spanners as individuals, we specifically highlight the important role of boundary spanning dyads and relationships.